Cytotoxicity of Dental Alloys - L. Vavřičková; T. Dostálová; D. Vahalová; J. Šrámková; J. Ulrichová (Czech Dental Chamber, 2007)
The paper presented cytotoxicity testing procedure in vitro of chosen nickel - chromium dental alloys - Remanium G soft, Wiron 99, Wirolloy a Heraenium NA. Direct contact test and extract test were used. A population of mouse desmocytes NIH 3T3 was used for both tests. Results show the all tested dental alloys can be considered noncytotoxic, with only small variation in extract test presented.